(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This thesis explores how nutrition influences the development of intestinal dysbiosis in children, focusing on the early formation of gut microbiota. It reviews current evidence on the impact of feeding methods, dietary components, and nutritional interventions. Key topics include the benefits of breastfeeding, effects of formula feeding, timing of complementary food introduction, and dietary strategies for managing dysbiosis. The study emphasizes the importance of evidence-based nutrition to support healthy microbiome development and prevent related health issues in pediatric populations.